Mediating effect of communication ethics practised on work ethics relationships with social media use, motives for using social media and internet surfing etiquette - Abdul Rahman, Mahfuzah; Wok, Saodah (2018)
Social media is a medium of communication nowadays. In fact, the accessibility of the Internet at the workplace makes it is easier for the users to use it either positively or negatively. Hence, this study tests the relationship between social media use, motives for using social media, Internet surfing etiquette, work ethics, and communication ethics. The Utilitarian Theory is used to see the benefits gained by the employees in terms of social media use at the workplace. This study applies the quantitative research design where a self-administered survey questionnaire is used as the instrument for data collection. Based on a sample of 344 respondents among the administrative staff of International Islamic University Malaysia (IIUM), the findings indicate that all variables are positively correlated with one another. Communication ethics fully mediates the relationship between social media use and motives for using social media towards work ethics. Communication ethics only partially mediates the relationship between the Internet surfing etiquette and work ethics. Therefore, communication ethics mediates the relationship between social media use, motives for using social media and Internet surfing etiquette towards work ethics.